Multicenter Reproducibility of sigma up 18 Theta -Fluciclatide PET Imaging in Subjects with Solid Tumors - Sharma, Rohini; Kallur, Kumar G; Ryu, Jin S; Parameswaran, Ramanathapuram V; Lindman, Henrik; Avril, Norbert; Gleeson, Fergus V; Lee, Jong D; Lee, Kyung-Han; O'Doherty, Michael J; Groves, Ashley M; Miller, Matthew P; et al. (The Journal of nuclear medicine (1978), 2015)
Integrins are upregulated on both tumor cells and associated vasculature, where they play an important role in angiogenesis and metastasis. Fluciclatide is an arginine-glycine-aspartic acid peptide with high affinity for ... integrin, which can be radiolabeled for PET imaging of angiogenesis. Thus, 18F-fluciclatide is a potential biomarker of therapeutic response to antiangiogenic inhibitors. The aim of this study was to evaluate the reproducibility of 18F-fluciclatide in multiple solid-tumor types. Thirty-nine patients underwent PET/CT scanning at 40, 65, and 90 min after injection of 18F-fluciclatide (maximum, 370 MBq) on 2 separate days (2-9 d apart). Patients did not receive any therapy between PET/CT scans. 18F-fluciclatide images were reported and quantitative measures of uptake were extracted using the PERCIST methodology. Intrasubject reproducibility of PET uptake in all measurable lesions was evaluated by calculating relative differences in SUV between PET scans for each lesion during the 2 imaging sessions. Thirty-nine measurable lesions were detected in 26 patients. Lesion uptake correlated strongly across imaging sessions (r = 0.92, P 0.05, at 40 min; r = 0.94, P 0.05, at 65 min; r = 0.94, P 0.05, at 90 min) with a mean relative difference and SD of the relative difference of 0.006 plus or minus 0.18 at 40 min, 0.003 plus or minus 0.19 at 65 min, and 0.025 plus or minus 0.20 at 90 min. This reflects 95% limits of repeatability of 35%-39% for the difference between the 2 SUV measurements or a variability of 18%-20% in agreement from that observed in well-calibrated multicenter 18F-FDG studies. The test-retest reproducibility of 18F-fluciclatide across multiple tumor types has been measured and shown to be acceptable. This is an important step in the development of this in vivo biomarker to identify and quantify response to antiangiogenic therapy in cancer patients. (ProQuest: ... denotes formulae/symbols omitted.)